DNA methylation episignature, extension of the clinical features, and comparative epigenomic profiling of Hao-Fountain syndrome caused by variants in USP7 - Laan, Liselot van der; Karimi, Karim; Rooney, Kathleen; Lauffer, Peter; McConkey, Haley; Caro, Pilar; Relator, Raissa; Levy, Michael A.; Bhai, Pratibha; Mignot, Cyril; Keren, Boris; Briuglia, Silvana; et al. (Genetics in medicine, 2024)
PURPOSE: Hao-Fountain syndrome (HAFOUS) is a neurodevelopmental disorder caused by pathogenic variants in USP7. HAFOUS is characterized by developmental delay, intellectual disability, speech delay, behavioral abnormalities, autism spectrum disorder, seizures, hypogonadism, and mild dysmorphic features. We investigated the phenotype of 18 participants with HAFOUS and performed DNA methylation (DNAm) analysis, aiming to generate a diagnostic biomarker. Furthermore, we performed comparative analysis with known episignatures to gain more insight into the molecular pathophysiology of HAFOUS. - METHODS: We assessed genomic DNAm profiles of 18 individuals with pathogenic variants and variants of uncertain significance (VUS) in USP7 to map and validate a specific episignature. The comparison between the USP7 cohort and 56 rare genetic disorders with earlier reported DNAm episignatures was performed with statistical and functional correlation. - RESULTS: We mapped a sensitive and specific DNAm episignature for pathogenic variants in USP7 and utilized this to reclassify the VUS. Comparative epigenomic analysis showed evidence of HAFOUS similarity to a number of other rare genetic episignature disorders. - CONCLUSION: We discovered a sensitive and specific DNAm episignature as a robust diagnostic biomarker for HAFOUS that enables VUS reclassification in USP7. We also expand the phenotypic spectrum of 9 new and 5 previously reported individuals with HAFOUS.